Patient Satisfaction Of Inpatient Social Security Administrator For Health In Hospital - Ida Nurmawati; Bunga Adina Pramesti (Universitas Muhammadiyah Malang, 2021)
Health service facilities were required to make patients satisfied. Therefore, good quality of service must be provided. In fact, many patients still feel dissatisfied. As many as 55.8% of the 129 patients said that the quality of BPJS services was not good and 44.2% of the 129 patients were not satisfied with the quality of service provided. These results were not appropriate with standards of inpatient satisfaction (≥ 90%). The purpose of this study was to analyze the quality of health services on patient satisfaction of inpatient BPJS. This study used the literature review method and found 15 journals and 2 undergraduate thesis that match with specified criteria. The results were found that the higher of quality service provided, so the higher of patients’ satisfaction and patients can felt satisfied if the patient wishes was fulfilled. Based on the results, hospitals should improve their services in accordance with patient expectations.